Enzymatic Transesterification Using Different Immobilized Lipases and its Biodiesel Effect on Gas Emission - Mohamad Nor, Nur Fatin Syafiqah; Veny, Harumi; Hamzah, Fazlena; Muhd Rodhi, Miradatul Najwa; Kusumaningtyas, Ratna Dewi; Prasetiawan, Haniif; Hartanto, Dhoni; Sulaiman, Sarina; Sazali, Rozana Azrina (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
Biodiesel, a third-generation bio-fuels, offering several advantages over regular diesel fuel. Waste cooking oil (WCO) emerges as an ideal feedstock due to its availability and easy accessibility. In this work, biodiesel is utilized from two different types of immobilized lipases: Rhizomucor miehei lipase (RMIM) and Candida antarctica lipase B (CALB). The impact of the molar ratio of oil to methyl acetate (1:3-1:12) was evaluated for both lipases, and the resultant biodiesel was tested in diesel engine. The enzymatic transesterification was carried out in ultrasonic assistance and the results showed that the greatest yield of 81.20% at 45℃, using CALB as a biocatalyst, 1.8% (w/v) lipase and oil to methyl acetate molar ratio of 1:12 within 3 hours. Triacetin, by-product was determined their concentration for each molar ratio and analyzed using FTIR range of 500cm-1 to 4000cm-1, revealing a significant absorption peak at 1238.90cm-1. Biodiesel was blended with commercial diesel fuel in varying quantities of 7, 10, and 20% by volume (B20). The results were compared to Industrial Diesel Fuel 7% (B7) and Commercial Diesel Fuel 10% (B10). NOx and CO2 emission drops as the percentage of diesel/biodiesel blends increases, supporting WCO as a cost-effective biodiesel feedstock with low petrol pollution.